Coordinated regulation of plant defense and autoimmunity by paired trihelix transcription factors ASR3/AITF1 in Arabidopsis - Wang, Ying (The New phytologist, 2023)
© 2022 The Authors. New Phytologist © 2022 New Phytologist Foundation.